Strengthening Accountability of Village Officers: The Effect of Competency, Commitment, and Community Participation - Sri Wahyuningsih; Mokhamad Natsir; Umu Khouroh (Innovation Business Management and Accounting Journal, 2026)
This study explores the factors that influence how transparently and responsibly village officials manage their duties, particularly in handling village fund allocations. As these officials hold significant responsibility for public resources, ensuring accountability is essential for effective local governance. The research focuses on three key areas: the professional skills of the staff, their loyalty to the organization, and the level of involvement from the local community. Data analysis was carried out using the Multiple Linear Regression Analysis method to test the influence of independent variables on the dependent variable both partially and simultaneously The findings reveal that the professional competence and expertise of village officials are the most critical factors in ensuring high-quality public service and reliable management. When officials possess the necessary knowledge and technical abilities, the overall standards of accountability improve significantly. Interestingly, the study found that internal commitment to the office and social oversight from residents do not yet play a major role in driving these standards at the local level. These results suggest that to achieve more professional and trustworthy village administration, the primary focus should be on enhancing the practical training and human resource development of the officials. By prioritizing skill-building, local governments can ensure that public funds are managed more effectively for the benefit of the community. Data analysis was carried out using the Multiple Linear Regression Analysis method to test the influence of independent variables on the dependent variable both partially and simultaneously.